The trees grew because I bled there: collected stories - LaRocca, Eric (Titan Books, 2023)
"Eight stories of literary dark fiction from a master storyteller. Exploring the shadow side of love, these are tales of grief, obsession, control. Intricate examinations of trauma and tragedy in raw, poetic prose. In these narratives, a woman imagines horrific scenarios whilst caring for her infant niece; on-line posts chronicle a cancer diagnosis; a couple in the park with their small child encounter a stranger with horrific consequences; a toxic relationship reaches a terrifying resolution...Originally published under the title The Strange Thing We Become and Other Dark Tales, this is a much-praised collection of deeply unsettling, painfully dark tales."--